Stimulasi Minat Berwirausaha Sejak Dini Dengan Bermain Peran Simulasi Bisnis Kelompok - Hasmawaty Hasmawaty; Delvhina Manga; Nurul Jamiah Sidiq; Faradilah Rusliana (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2026)
Instilling an interest in entrepreneurship from an early age is very important for shaping a strong, innovative, and independent character in children, given that this increasingly competitive era demands the development of soft skills and entrepreneurial character. Until now, entrepreneurial learning practices in early childhood education have tended to focus on basic academic aspects without concrete contextual experiences in optimally fostering an interest in entrepreneurship. This study aims to examine the effect of role-playing on increasing entrepreneurial interest in early childhood through a role-playing approach and group business simulation. The method used was a quasi-experiment with a sample of all 20 students in group B at Al Izhar Kindergarten in Makassar. Data were collected using observation and a Likert scale to measure the variables of entrepreneurial interest, which included confidence, communication, and negotiation. The results showed that the use of role-playing media significantly increased entrepreneurial interest in early childhood by developing children's creativity, confidence, communication, and negotiation skills. These findings confirm that play media, particularly through role-playing and business simulation, is an effective strategy in instilling the basics of entrepreneurship from an early age and supporting the development of children's character and competencies.